LANGUAGE TEACHER POSITIONING IN A TEACHER PROMOTION EXAMINATION: A SMALL STORY APPROACH - Werbińska, Dorota (Neofilolog, 2020)
Although there is an increasing body of research on diverse aspects of language teachers’ professional practice there are still contexts that remain hardly explored. One such context is the oral examination situation encountered by experienced language teachers in Poland who aspire to be promoted in the ranks of the teaching profession. Drawing on positioning theory as a methodological tool to analyse the experience of one English teacher’s promotion examination situation, I will attempt to find out what aspects of teacher identity emerge from the small stories employed in the examination situation, as well as what lessons can be learnt from a study about teacher positioning (both self-positioning and being positioned) in the professional assessment context. Although the study is set in the Polish context, it may contribute to the knowledge on language teacher identity (re)construction in general through its focus on one area of language teacher professional practice – taking a teacher promotion examination.